Numerical Analysis of Nonlinear Dynamics of an Offshore Platform for Energy Harvesting - Ribeiro, Mauricio A.; Tusset, Angelo Marcelo; Lenz, Wagner B.; Balthazar, José Manoel [UNESP]; Litak, Grzegorz (Springer Nature, 2024)
In this work, we numerically investigate the nonlinear model that describes the displacement of an offshore platform under ocean wave action. However, we have coupled a piezoceramic based system for the possible analysis of the generated energy that the system can produce. And so, a proposal for a pilot model for energy collection. For our analysis we investigate the behavior of the attraction basins described by the initial conditions of the system dynamics. Thus, we identified that the attraction basins have the sifting phenomenon with the variation of the parameter p. Other analyzes performed were the Maximum Lyapunov Exponent to determine the parametric set for dynamic regions where the system is in a chaotic or periodic regime. This behavior affects energy production, as the values that determine the maximum power have a positive LME exponent. We also determined the chaotic and periodic phase map as we observed in the results.
Keywords: Basins of attraction; Dynamics system; Offshore platform